2010
DOI: 10.1111/j.1741-2358.2010.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible relationship between periodontitis and dementia in a North Indian old age population: a pilot study

Abstract: Possible relationship between periodontitis and dementia in a North Indian old age population: a pilot study Background: Periodontitis and cognitive impairment or dementia is relatively common among older adults. Few cross-sectional studies and some longitudinal studies have attempted to link oral health with dementia diagnosis or disease pathology but none has investigated the role of inflammation as a potential mediator. Objectives: This study was planned to establish a relation of inflammatory mediators bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 17 publications
3
63
1
2
Order By: Relevance
“…Most recently, significantly higher serum CRP, MMP‐8, MMP‐9, TNF‐α levels have been reported in dementia and periodontitis patients in comparison with HC (Rai et al. ). Increased amounts of MMP‐8 (as well as MMP‐1, ‐3 and myeloperoxidase) in saliva and the presence of putative periodontal pathogens in HIV‐patients’ periodontal pockets have been reported (Mellanen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, significantly higher serum CRP, MMP‐8, MMP‐9, TNF‐α levels have been reported in dementia and periodontitis patients in comparison with HC (Rai et al. ). Increased amounts of MMP‐8 (as well as MMP‐1, ‐3 and myeloperoxidase) in saliva and the presence of putative periodontal pathogens in HIV‐patients’ periodontal pockets have been reported (Mellanen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although investigators in cross-sectional studies 14,20,21 and a prospective study 19 found that biological markers for periodontal infection were associated with dementia or cognitive impairment, studies in which researchers have investigated these associations by using clinical signs of periodontal disease (for example, pocket depth, gingival bleeding or attachment loss) have shown mixed results. 2,5,7,8,11,18,22,23 Possible reasons for this variability are that many of these studies had small numbers of participants, 7,18 and some studies relied on measures of periodontal disease that are based on partial examinations 8,22 or self-report.…”
mentioning
confidence: 99%
“…Las enfermedades orales más comunes encontradas en pacientes ancianos y más aún con demencia o algún tipo de discapacidad, se asocian a la presencia de placa bacteriana: caries dental y enfermedad periodontal, debido principalmente a la dificultad de realizar la higiene oral, a los cambios en la dieta y a la hiposalivación relacionada con el consumo de medicamentos (12,21,(25)(26)(27).…”
Section: B Sintomatologíaunclassified